A BUSCA DA HEGEMONIA: A SAGA DO MASCULINO EM WORLD OF WARCRAFT - Dall Pozzo, Bryan Rafael (2017)
In the past decades, there is an increasing number of masculinities that can be observed in movies, books, magazines, series and games. In these, symbols of virile masculinity spread out rapidly and continuously. The questioning of the concept of masculinity and its social implications bases on the perspective that there is a unique and unquestioned hegemonic masculinity, built on the domination and on the incontestable power of patriarchalism. In contemporary times, arise questions as for the universality of this declared male supremacy, since it can be found many incompatibilities between models of male power and the living experiences of countless men, which often fail to achieve this hegemonic status, staying on the margins of this declared hegemonic manhood. Thus, emerge several male models that can be widely observed through media, such as games. Basing on the studies of gender of Robert Connell (1997), Elisabeth Badinter (1993), Socrates Nolasco (1993) and Michael Kimmel (1997), and through a Cultural Studies perspective represented by Stuart Hall (2003) and Zygmunt Bauman (2005), we deepen in the narrative present in the fictional universe of the computer game World of Warcraft, with the purpose of identifying discourse strategies used on representations of masculinity models and identities of two characters present on the computer game, aiming the perception of strengthening mechanisms of gender stereotypes. World of Warcraft fictional universe has forms, races, religions, and its own fauna and flora, and although its story and narrative form part of a fictional literature context, there are several social and cultural representations that can be observed in the characters, stories and their relations. We observe the masculinities because they have, in addition to the hegemonic and marginalized representations of what is being a man, fragmentations of identity, which can also be observed on the players, given that they are in direct contact with the game universe, taking part in it and entering its struggles, representations, marginalization and hegemonic powers. Finally, the discursive strategies present in the representation of masculinities archetypes, in this game, is in accordance with the hegemonic masculinity that is imposed to men, reinforcing gender stereotypes and identity fragmentation, finding correspondence in current models and architypes that regulate the social and cultural masculine world.